The oasis guide to asperger syndrome : completely revised and updated. Advice, support, insight, and inspiration. - Romanowski, Patricia (Crown Publisher, 2005)
As is one of those unusual condictions that is a mix of both disability and, at times, talents. It is very easy to misrepresent. As by focusing on just one of these two aspects.